The Influence of Customer Relationship Management and Switching Barrier on Customer Loyalty at PT. Permodalan Nasional Madani (PNM) in Pasaman District - Erdawati; M. Yudha Prayoga; Mai Yuliza; Jayasman (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
Permodalan Nasional Madani (PNM) is an institution that distributes funds to the community in the form of business capital to help the community's economy. The purpose of this study is to see the influence of Customer Relationship Managementand Switching Barriers to Loyalty at PT. Permodalan Nasional Madani (PNM) The method used in this study is a quantitative method. Data collection in this study was through a questionnaire distributed to 60 respondents.The method used in this study is non-probability sampling.The results of the study show that the variables: a).Customer Relationship Management Has a positive and significant influence on Loyalty with valuet count is 3.415 with a significant level (Sig. 0.000.)b).Switching Barrierhas a negative and significant effect on loyalty with a t-value of (-2.048) and a sig. value of 0.045. c).Customer Relationship Management Variables andVariablesSwitching BarriersThe F test value is 54.683 and the significance value is 0.000. Simultaneously, there is an influence of the Customer Relationship Management variable And Switching Barrierson Customer Loyalty. Contribution of Customer Relationship Management variables and Switching Barriers as big as0.657, on the Customer Loyalty variable or 65.7% and the remaining 34.3 is influenced by other variables. From the results it is suggested PT. Madani National Capitalneed to increase customer loyalty by maintaining long-term relationships, intense interaction with customers maintaining and relational benefits, as well as the availability and attractiveness of alternatives to PT. PNM. Keywords : Customer Relationship Management, Switching Barrier, Loyalty